ACTIVATION OF THE DEVELOPMENT OF CREATIVE COGNITIVE THINKING OF PRESCHOOL CHILDREN - Ganieva Vazira Yusufona (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The development of preschool education with the transition to a new quality level cannot be carried out without the development of innovative technologies. The traditional methods are being replaced by active teaching and upbringing methods aimed at enhancing the creative cognitive development of the child. Therefore, it is necessary to introduce modern methods and technologies into the learning process, and also, in these changing conditions, the teacher of preschool education needs to be able to navigate in a wide range of modern pedagogical technologies.